Ptyctimous mites (Acari, Oribatida) of Victoria (Australia) - Niedbała, Wojciech; Szywilewska-Szczykutowicz, Anetta (Zootaxa, 2017)
A list of 37 species of ptyctimous mites from the State of Victoria, Australia, is provided. Seven species new for science are described and further seven are recorded for the first time in Victoria. The genus Arphthicarus has been discovered in Victoria and is represented by two new species. Zoogeographical distribution of each species is provided. Analysis of the ptyctimous fauna from four Victorian areas (Otway Ranges, Yarra Ranges, Errinundra Plateau and Strzelecki Ranges) has revealed that four species occur in a large number of specimens in one of the areas. Similarity analyses indicate that the faunas of Errinundra Plateau and Yarra Ranges are the most similar. An overview of state of knowledge on the ptyctimous mites from State of Victoria, Australia and Australasian Region is presented.